The Usborne art treasury - Dickins, Rosie; Butler, Nicola (Tulsa, Okla. : EDC Pub., 2006)
Showcases twenty-two significant works of art, each with brief biographical information about the artist, and instructions for a project that mimics the artist's style or technique.
"Picture, paintings, and projects"--Cover.
3.9
K-3
Keywords: Art appreciation -- Juvenile literature; Art -- History -- Juvenile literature; Art appreciation; Art -- History; Art appreciation; Art -- History